The Influence of Internal and External Factors on Non-Performing Loans In Indonesia's Largest Banking Industry - Lasty Agustuty; Riza Praditha; Robert Jao; Andi Ruslan (Universitas Muhammadiyah Sorong, 2022)
This study aims to measure the effectiveness of internal factor proxies from the aspect of efficiency as measured by the ratio of operating costs and operating income (BOPO), liquidity as measured by the loan-deposit ratio (LDR), bank size as measured by total assets, and aspects of bank capital that measured by the capital buffer and external factors using the Repo Rate, and inflation on non-performing loans in the ten largest banking industries in Indonesia. The sample consists of the 10 largest banks in Indonesia with the criteria of having total bank assets of the total national banking assets above 2%. The data used are annual data from 2011 to 2020. The results show that from the bank's internal factors, BOPO has a positive and significant effect on the NPL. LDR, and variable capital buffer, a negative and significant on NPL. While the size of the bank obtained results that are not significant to the NPL. From external factors, the results obtained where interest rates have a significant negative effect on NPLs while inflation is not significant for increasing NPL.